Marginal adaptation of 3D-printed crowns: influence of preparation geometry and digitization workflow - Khalid Abdelsalam; Ahmed Attia (BMC Oral Health, 2026)
Abstract Background This in vitro study evaluated the impact of different workflow and finish line design on the marginal adaptation of 3D printed resin matrix ceramic crowns. Methods Forty extracted mandibular molars were randomly allocated into two groups according to finish line design ( n = 20); heavy chamfer 0.8 mm (H) and conservative chamfer 0.2 mm (C). Each main group was divided into 2 subgroups ( n = 10) according to workflow; direct digital intraoral scanning workflow (D) and semi-digital workflow (S). Crowns were 3D printed from hybrid resin and cemented using adhesive resin cement. Marginal adaptation was evaluated for all groups using a stereomicroscope before cementation and after the combined cementation and artificial aging. Statistical analysis was performed with 3-way ANOVAs and post hoc Tukey test, ( P < 0.05). Results Significant effects were found for finish line design, workflow, and the combined cementation and artificial aging ( P < 0.05), with no significant interaction between finish line design and workflow ( P = 0.552). Mean marginal gaps (µm) of test groups before cementation and after the combined cementation and aging protocol were: HD, (71.72 ± 4.82), (84.5 ± 2.75); CD, (82.16 ± 3.76), (97.32 ± 3.16); HS, (92.51 ± 3.64), (111.8 ± 3.37); and CS, (106.1 ± 3.57), (123.4 ± 2.58). All groups showed significant increases thereafter ( P < 0.05). Heavy chamfer finish line and direct digital workflow each yielded significantly smaller marginal gap than conservative chamfer and semi-digital workflow at both time points ( P < 0.05). Conclusions Within the limitations of this in vitro study, finish line design and workflow type each independently influenced the marginal adaptation of 3D-printed resin matrix ceramic crowns. A heavy chamfer and a direct digital workflow were each associated with smaller marginal gaps.